Platelets in Inflammation and Atherogenesis - Nording, Henry M.; Seizer, Peter; Langer, Harald F. (Frontiers in Immunology, 2015)
Platelets contribute to processes beyond thrombus formation and may play a so far underestimated role as an immune cell in various circumstances. This review outlines immune functions of platelets in host defense, but also how they may contribute to mechanisms of infectious diseases. A particular emphasis is placed on the interaction of platelets with other immune cells. Furthermore, this article outlines the features of atherosclerosis as an inflammatory vascular disease highlighting the role of platelet crosstalk with cellular and soluble factors involved in atheroprogression. Understanding, how platelets influence these processes of vascular remodelling will shed light on their role for tissue homeostasis beyond intravascular thrombosis. Finally, translational implications of platelet-mediated inflammation in atherosclerosis are discussed.